The impact of financial accountability, public monitoring and local head tenure on local government performance - Muhtar Muhtar (Universitas Sebelas Maret, 2022)
The study aims at examining the effect of financial accountability, public monitoring, and local head tenure on local government performance in Indonesia. Employing secondary data obtained from the governing bodies in Indonesia, the research generates 508 local governments during 2018-2019 with total of 1016 observations analyzed with panel data regression. Overall, the local governments in Indonesia in average has been able to reach high level performance despite there are still several local governments with only medium level. The empirical analysis reveals that local government financial accountability and public monitoring have positive effect on local government performance. However, local head tenure has no significant effect on local government performance. The study provides several recommendations to improve local government performance. Firstly, local governments should put various efforts in realizing proper financial accountability by improving the governance from budgeting, realization, and financial reporting while also having adequate internal control and procedures. Secondly, the public should have considerable attention on local government activities in performing its functions and responsibilities in which public participation and democratic environment should be maintained.